The European Union as a civilian power: The case of the eu’s trade policy - Özer, Yonca (Marmara Üniversitesi Avrupa Birliği Enstitüsü, 2012)
This study addresses what characterises the EU’s role as an international actor by drawing on ‘civilian power Europe’ role concept as a fruitful point of reference. It analyses the scope of the concept from a broad point of view including the other characteristics of a civilian power instead of a narrow focus on the civilian versus military debate with a special empirical reference to the EU’s trade policy as Europe’s most long-standing and most powerful external policy realm. The study argues that EU’s trade policy mostly reflects ‘civilian power’ character of the EU.
Keywords: Civilian Power, Civilian Power Europe, EU, Trade Policy, EU’s trade policy